Winged Prometheans: Arctic Aviation as Socialist Construction in Stalinist Russia, 1928-1939 - McCannon, John (Scientia Canadensis, 2010)
During the 1920s and especially the 1930s, aviation became an increasingly important tool in the exploration and development of the USSR’s Arctic territories. The deployment of aircraft proved a boon to scientific research, but Soviet priorities in the Arctic during these years, particularly with the advent of Stalin’s five-year plans from 1928 onward, were more about building infrastructure and realizing the region’s potential for resource extraction. The use of aircraft in the Soviet Arctic was affected accordingly, with economic and developmental needs privileged over scientific ones. In line with its cultivation of pilots as national heroes, the Stalinist regime also took advantage of the international and domestic popular appeal of polar aviators—and the many exploits they staged in 1928 and afterward—to generate positive publicity for itself. Integrating Arctic aviation into the larger cultural framework of socialist realism, the USSR’s state-controlled media complex transformed polar fliers into symbols of Soviet virtue, exemplifying not just trailblazing courage, aptitude, and the mastery of futuristic technology—motifs common to the aviation cultures of many countries during this era—but also self-discipline and collective effort on behalf of the Soviet homeland and the attainment of socialist utopia.